Efficacy and Safety of G2013 as a Novel Immunosuppressive Agent on Differentiation, Maturation and Function of Human Dendritic Cells - Nazanin ARJOMAND FARD; Nakisa TABRIZIAN; Reza MIRZAEI; Jamshid HADJATI; Farzaneh TOFIGHI ZAVAREH; Ali Reza SALEHI NODEH; Abbas MIRSHAFIEY (Tehran University of Medical Sciences, 2017)
Background: The expanse of dendritic cells (DC) differentiation plays an important role in determining immune response. DC-based immunosuppressive drugs have notable side effects in increasing the risk of infectious diseases and cancers. G2013, as a novel anti-inflammatory and immunosuppressive agent, has been tested in experimental model of multiple sclerosis. The aim of this study was to conduct the safety property of G2013 on dendritic cells biology. Methods: The effect of G2013 on differentiation, maturation, and function of dendritic cells was examined at Tehran University in 2014. To investigate how G2013 affects human dendritic cells (DC) in a defined inflammatory environment, human peripheral blood mononuclear cells (PBMC) were isolated from healthy blood. Monocytes were then purified using anti-CD14 microbeads. Monocytes were treated with G2013 in two different doses (6 and 12 μg/well) along with adding granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-4 for inducing monocytes to immature DC and adding lipopolysaccharide for running DC maturation. Differentiation, maturation, and function of dendritic cells were examined with flow cytometry and ELISA. Results: G2013 therapy had no significant effect on CD83, CD86 and DR expression, as well as IL-10 and IL-12 cytokine levels and it, has no remarkable side on differentiation, maturation and function of dendritic cells in immature DC and mature DC process in vitro. Conclusion: G2013 is a safe agent with no adverse effect on differentiation, maturation, and function of dendritic cells. It may be recommended as a novel immunosuppressive agent with no or little side effect in increasing the risk of infectious diseases and cancers.